صكوك الإجارة السيادية في نيجيريا بين الالتزام بالمعايير الشرعية وتحديات التطبيق: دراسة وصفية تحليلية: Ijarah Sukuk in Nigeria: Between Compliance with Shariah Standards and Practical Challenges - Muhammad Bello, Aliyu; Saleh, Abdulmajid Obaid Hasan (International Journal of Al-Turath In Islamic Wealth and Finance, 2025)
الملخص تُعد تجربة إصدار صكوك الإجارة السيادية في نيجيريا مثالًا مهمًّا على توظيف أدوات التمويل الإسلامي في بيئة قانونية واقتصادية لا تستند في أساسها إلى الشريعة الإسلامية. يهدف هذا البحث إلى بيان المفهوم الشرعي لصكوك الإجارة وخصائصها، وتحليل مدى التزام التجربة النيجيرية بالضوابط والمعايير الشرعية، فضلًا عن استعراض أبرز التحديات المؤسسية والتشريعية التي تعيق التطبيق الأمثل. وقد اعتمدت الدراسة على المنهج الوصفي التحليلي، مستندةً إلى المصادر الفقهية والمعايير الصادرة عن الهيئات المعتمدة، إضافة إلى التقارير الرسمية والدراسات الحديثة ذات الصلة. أظهرت النتائج أن الهيكلة المعتمدة في الإصدارات النيجيرية التزمت بعدد من الضوابط الشرعية الجوهرية، مثل وجود أصل مؤجَّر حقيقي، وتخصيص العائد على هيئة دفعات إيجارية دورية، وعدم تضمين ضمان صريح لرأس المال أو العائد. ومع ذلك، برزت بعض الإشكالات، أهمها غياب الإطار القانوني الشرعي المتكامل، وضعف الكفاءات المتخصصة، ومحدودية الرقابة الشرعية، إضافة إلى ملاحظات تتعلق بوضوح المنفعة وآليات تحمّل المخاطر. وتوصي الدراسة بضرورة إنشاء هيئة شرعية مستقلة، وتطوير الأطر التشريعية والتنظيمية، وتأهيل الكوادر البشرية، وتوسيع نطاق التوعية المجتمعية بالتمويل الإسلامي، بما يعزز استدامة هذه التجربة وتوافقها الكامل مع أحكام الشريعة الإسلامية. Abstract The issuance of sovereign Ijarah sukuk in Nigeria represents a significant example of applying Islamic finance instruments within a non-Arab, non-Islamic legal and economic environment. This study aims to outline the Shariah concept and characteristics of Ijarah sukuk, examine the extent to which the Nigerian experience complies with established Shariah standards, and identify the key institutional and legislative challenges hindering optimal implementation. The research adopts a descriptive-analytical methodology, drawing on classical jurisprudential sources, standards issued by recognized Shariah bodies, as well as official reports and recent academic studies. The findings reveal that the adopted structures in Nigerian issuances adhere to several core Shariah requirements, such as the existence of a genuine leased asset, distribution of returns as periodic rental payments, and the absence of explicit guarantees for principal or profit. Nevertheless, certain issues persist, including the absence of a comprehensive Shariah-compliant legal framework, limited specialized expertise, insufficient Shariah oversight, and concerns regarding the clarity of usufruct definition and risk-sharing mechanisms. The study recommends establishing an independent national Shariah board, enhancing legislative and regulatory frameworks, developing human capital, and expanding public awareness of Islamic finance to ensure the sustainability of the experience and its full alignment with Islamic principles.